RED VELVET COOKIES WITH SUBSTITUTION SEAWEED FLOUR (Eucheuma cottonii) SEBAGAI CEMILAN SEHAT FOR THE GENERATION MILENIALS - Ali, Lisa Ariska; Hamidah, Siti (Prosiding Pendidikan Teknik Boga Busana, 2021)
Culinary in Indonesia is now experiencing a lot of shifts with the emergence of various kinds of fast food which are in demand by various groups. Therefore, as part of the millennial generation who understands technology in the food sector, of course they can choose healthy foods to consume. One of the healthy food ingredients that can be processed from fisheries is seaweed flour (Eucheuma cottonii). Processed from seaweed flour is still minimal, especially in the field of pastry. In this research, we will process cookies with seaweed flour substitution. Seaweed flour which has a lot of vitamin extract. Winarno, (2002: 67) states that foods that contain lots of vitamins come from the sea. So that this seaweed flour can be used as a substitute for red velvet cookies as a millennial snack. Keywords: red velvet cookies, seaweed flour, millennial generation.